Understanding and Addressing Problems in Research Collaboration: A Qualitative Interview Study From a Self-Governance Perspective - Meißner, Florian; Weinmann, Carina; Vowe, Gerhard (Frontiers in Research Metrics and Analytics, 2022)
For collaborative research to be successful, understanding and solving collaboration problems is of paramount importance. However, theory-driven research on this issue at a general level is scarce. Drawing from two micro-oriented approaches (i.e. club theory and commons theory) and relying on self-governance as the basic principle for addressing collaboration problems, we aim to develop theoretically informed, concise and generalizable catalogues of problems and solutions based on the experiences and expectations of research collaboration participants. A series of expert interviews (N = 18) were conducted with leading researchers in Germany. Seven typical problems (e.g. lack of commitment or fairness) and twelve possible solutions (e.g. continuous evaluation or creating cognitive common ground) that can be applied within the self-regulatory framework were identified. The results provide a useful framework to further investigate problems and solutions as well as interlinkages between the two, and to improve research collaboration.